Avaliação da efetividade de diferentes produtos na redução da permeabilidade da dentina radicular e resistência a desafios ácidos - Domingues, José Eduardo Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of the study was to evaluate in vitro the effectiveness of different desensitizing agents for the treatment of cervical dentinal hypersensitivity in the reduction of dentine permeability and resistance to challenges with different acids of diet. Material and Methods: Were used, 75 freshly extracted third molars. The crowns of these teeth were sectioned at the cementum-enamel junction, the pulp tissues were removed and the cervical root dentins were exposed using a cylindrical drill associated with a high speed device (1 mm of deepness). Only these parts of the teeth were exposed because the rest was covered with black enamel. These 75 specimens were randomly allocated in three groups of 25: I -Biosilicato®, II - Colgate Sensitive Pró-Alívio® e III - Desensibilize Nano P® . The specimens were fixed to a hydraulic pressure device for assessing the variation in the dentine permeability after treatments with the desensitizing agents and after acid challenges with different beverages. The dentine permeability was measured after the following sequential steps: (1) after the acid etching of the specimens; (2) after the application of the desensitizing agents; (3) After three sequential acid challenges with different commonly consumed substances (Lemon, vinegar, white wine, coke®, energetic). Kruskall-Wallis teste, Bonferroni multiple comparison and nonparametric ANOVA with repeated measures they were applied for the statistical analysis and the significance level was set to 0.05. Results: All the desensitizing agents were effective to reduce the dentine permeability (p <0.001). Additionally, the Biosilicate® group showed a lower residual dentine permeability (32.98±13.71%) compared with the groups of samples treated by the Colgate Sensitive Pro-Relief® (53.14% ± 13:30) and with the Desensitive Nano P® (55.82±17.35%) (p <0.001). It was showed that all the substances...(Complete abstract electronic access below)

O objetivo deste estudo foi avaliar in vitro a efetividade de diferentes agentes dessensibilizantes para tratamento da hipersensibilidade dentinária cervical (HSDC), na redução da permeabilidade dentinária e resistência a desafios ácidos da dieta. Material e métodos: Foram utilizados 75 dentes terceiros molares recém extraídos, seccionadas as coroas dentárias ao nível da junção cemento-esmalte, o tecido pulpar removido e a dentina radicular cervical exposta utilizando uma fresa cilíndrica de alta rotação (aproximadamente 1 mm de profundidade); somente esta parte do dente ficou exposta, pois o restante foi coberto com esmalte preto. De cada raiz um espécime foi preparado, totalizando 75 espécimes distribuídos randomicamente em três grupos de 25: I -Biosilicato®, II - Colgate Sensitive PróAlívio® e III - Desensibilize Nano P® . Os espécimes foram fixados a um aparelho de pressão hidráulica para avaliar as alterações na permeabilidade da dentina após os tratamentos com os agentes dessensibilizantes e após desafios ácidos. A permeabilidade da dentina foi medida após as seguintes etapas sequenciais: (1) após condicionamento ácido dos espécimes; (2) após tratamento com os agentes dessensibilizantes; (3) após três desafios ácidos sequenciais com diferentes substâncias comumente consumidas (limão, vinagre, vinho branco, Coca Cola® e Red Bull®). Os testes de Kruskall-Wallis, comparações múltiplas de Bonferroni e ANOVA não paramétrica com medidas repetidas foram aplicados para a análise estatística dos dados e o nível de significância considerado foi de 5% (p<0.05). Resultados: Todos os produtos foram eficazes na redução da permeabilidade dentinária (p<0.001). Adicionalmente foi verificado que a permeabilidade residual foi menor no grupo de amostras tratadas com Biosilicato® (32.98±13.71%) em relação ao grupo de amostras que foram tratadas...(Resumo completo, clicar acesso eletrônico abaixo)
Evaluation of the effectiveness different products in reducing the permeability of root dentin and resistance to acids challenges
Keywords: Ácidos; Dentina - Sensibilidade; Acids